1 0 2 D O C U M E N T 9 0 O C T O B E R 1 9 2 5 Zurich[4] and through Anschütz.[5] However, that should only be done if the danger is really imminent. What do you think? It does seem to me that evil could still be averted with patience... Remember, apropos, the biblical saying: he who visits your sins on your children, grandchildren, and great-grandchildren.[6] Send me your opinion again very soon, your Albert 90. From Hendrik A. Lorentz Haarlem, 18 October 1925 Dear Colleague, When recently I read your paper: “Unified Field Theory of Gravitation and Electricity”[1] (it is probably the paper of which you showed me a proof in Geneva[2] ), for a moment the thought occurred to me that if the vector is set equal to zero it could perhaps lead to an inconsistency. It turned out that this is not the case in the case you consider in §3 and I am mentioning this idea only because it led me to attempt a solution to the equations in which one does not posit from the outset.[3] Such a solution really can be offered, if the values for the ’s are constrained to ones that differ only infinitesimally from the system , , for . Thus I stipulate and view as infinitely small to first order it is also assumed of all ’s for that they are infinitesimal to this order of magnitude likewise for all ’s and for . Quantities of second rank should be neglected. Furthermore, the separate into a symmetric component and an antisymmetric com- ponent. Let the first be called , the second (you write ) hence , After establishing these, one can write and for , (1) If, as here, an infinitely small factor follows, the ’s and ’s can be substituted by the values –1 or +1. This notation (1) just ascertains that we always have the correct sign without always having to distinguish between the indices 1, 2, 3, on the one hand, and 4, on the other hand. ϕα ϕα 0= gαβ g11 g22 g33 1– = = = g44 1= gαβ 0= α β ≠ g11 1– γ11, + g22 1– γ22, + g33 1– γ33, + g44 1 γ44 + = = = = γ11, γ22, γ33, γ44 gαβ α β ≠ Γμν α ϕα gαβ α β)’s ≠ ( γαβ ψαβ ϕαβ gαβ γαβ ψαβ += γβα γαβ = ψβα ψαβ –= gαα gαα --------1 -= α β ≠ gαβ gαα gββ gβα –= gβα) ( gαα gββ